PARADIGMA MISI KRISTEN DALAM ERA PLURAL, : Memoderasi Dinamika Relasi Agama di antara Spontanitas Kemanusiaan dan Legalistik Transaksional - Rannu Sanderan; Feky Markus; Polina Ulpa; Rati Datukayang; Nelchy Boboy; Albir Resua (Melo: Jurnal Studi Agama-agama, 2023)
Abstract : The purpose of this research is to explore the social diversity experienced by Christians (the Church), which dynamically manifests varied attitudes and responses. This research article explores the significance of Christian mission in fostering interreligious dialogue in the context of everyday human life, encompassing both fundamental cooperation and the resolution of social issues. The theoretical approach employed revolves around the construction of religious diversity in an increasingly pluralistic society, as well as an understanding of social and cultural values as the foundation of human interaction. The study highlights the need to reconstruct the understanding of Christians regarding religious pluralism, by referring to biblical guidance that acknowledges the existence of other religious individuals and an understanding of God's salvific work encompassing multiple traditions and paths. However, challenges persist in the attitudes and understanding of Christians towards other religions, including exclusive and superior attitudes, as well as transactional and legalistic perspectives that hinder productive dialogue. Additionally, issues of tolerance, justice, migration, globalization, and sustainable development are also of concern in the context of Christian mission. The findings of this research contribute to depicting the complexities and challenges faced in the current context of Christian mission, while providing a foundation for the development of more inclusive, sustainable, and responsive approaches and practices towards social and environmental dynamics. Abstrak: Tujuan dari penelitian ini adalah untuk mengeksplorasi fakta keragaman sosial yang dialami orang Kristen (Gereja), yang secara dinamis menunjukkan sikap dan tanggapan yang berbeda-beda. Artikel penelitian ini mengeksplorasi pentingnya misi Kristen menghidupkan dialog antaragama dalam konteks kehidupan kemanusiaan sehari-hari, baik dalam hal kerjasama fundamental maupun penyelesaian masalah sosial. Pendekatan teoritik yang digunakan adalah konstruksi keberagaman agama dalam masyarakat yang semakin majemuk, serta pemahaman tentang nilai-nilai sosial dan kultural sebagai dasar interaksi manusia. Penelitian ini menyoroti perlunya merekonstruksi pemahaman Gereja terhadap pluralitas agama dengan merujuk pada panduan Alkitab yang mengakui keberadaan orang beragama lain dan pemahaman tentang karya penyelamatan Allah yang melibatkan banyak tradisi dan cara. Namun, masih terdapat tantangan dalam sikap dan pemahaman orang Kristen terhadap agama-agama lain, seperti sikap eksklusif, superior, dan pemahaman transaksional legalistik yang menghambat dialog yang produktif. Selain itu, masalah toleransi, keadilan, migrasi, globalisasi, dan keberlanjutan pembangunan juga menjadi perhatian dalam konteks misi Kristen. Hasil penelitian ini berkontribusi dalam menggambarkan kompleksitas dan tantangan yang dihadapi dalam konteks misi Kristen saat ini, serta memberikan landasan bagi pengembangan pendekatan dan praktik yang lebih inklusif, berkelanjutan, dan responsif terhadap dinamika sosial dan lingkungan.